PENGARUH PSAK NO. 1 TENTANG PENYAJIAN LAPORAN CASH FLOW DAN CAPITAL EXPENDITURE TERHADAP FIRM VALUE PADA PERUSAHAAN YANG BERGERAK DI BIDANG CONSUMER GOOD YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2010-2019 - Gina Sakinah; Ade Ponirah (UIN Sunan Gunung Djati Bandung, 2021)
Financial statements are prepared and presented to be submitted to those who need them. Of course, in this presentation must be in accordance with the existing provisions that are stipulated in PSAK No. 1 concerning the presentation of financial statements. Firm Value has an important role because it will form an image for the company, firm value is created by the contribution of other factors. Operation Cash Flow informs cash inflows and cash outflows from a company. Capital Expenditure as a reserve fund to support the expansion of the company or the improvement of assets. This research uses descriptive methods and quantitative approaches using secondary data supported by literature and documentation studies. The results showed that Operation Cash Flow partially has a positive and significant effect on Firm Value as well as Capital Expenditure has a positive and significant effect on Firm Value. Simultaneously both free variables can contribute and are able to significantly affect firm value.Keywords: Operation Cash Flow, Capital Expenditure, Firm Value